RANCANG BANGUN VISUALISASI TOURISM GUIDE PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Jeffry Andhika Putra; Rusdy Agustaf (Universitas Janabadra, 2019)
Tourism objects in the Special Region of Yogyakarta are quite interesting to visit. By looking at various kinds of tourist objects, both natural tourism and cultural tourism that can be developed into tourism destinations.The media needs of Yogyakarta tourism promotion still need development. With the internet that facilitates cross-information, it is necessary to build a tourism information system in the Special Region of Yogyakarta in the form of interactive websites, so that the information presented is more interesting.The website that was built covers all tourism objects in Yogyakarta, contains addresses, location images, and a brief description of sound and text. With this website, visitors are expected to be facilitated in finding information and increasing tourist visits to the Special Region of Yogyakarta. Keywords: information, tourism object, internet, website.